Las normas de jus cogens en diálogo con Norberto Bobbio. Justicia, validez, eficacia y otros criterios de análisis - Rosales Zamora, Pablo (Pontificia Universidad Católica del Perú, 2025)
The purpose of this paper is to analyze the norms of jus cogens through the lenses of justice, validity, and efficacy, as proposed by Norberto Bobbio from the perspective of the general theory of law. For this analysis, the «Draft Conclusions on the Identification and Legal Consequences of Peremptory Norms of General International Law (Jus Cogens)» (2022) and the doctrine on jus cogens are reviewed. Furthermore, two additional criteria not addressed by Bobbio are proposed: the political factor and efficiency, aimed at analyzing peremptory norms of general international law.

El presente trabajo tiene como finalidad analizar las normas de jus cogens bajo los criterios de justicia, validez y eficacia que aporta Norberto Bobbio desde la teoría general del derecho. Para este análisis, se revisa el «Proyecto de Conclusiones sobre la Identificación y consecuencias jurídicas de las normas imperativas de derecho internacional general (ius cogens)» (2022) y lo que la doctrina señala acerca del jus cogens. Asimismo, se proponen dos criterios adicionales no contemplados por Bobbio: el factor político y la eficiencia, para el estudio de las normas perentorias del derecho internacional general.
Jus Cogens Norms in Dialogue with Norberto Bobbio. Justice, Validity, Effectiveness, and Other Criteria of Analysis
Keywords: Bobbio; International law; Jus cogens; International norm; General theory of law; Bobbio; Derecho internacional; Jus cogens; Norma internacional; Teoría general del derecho; https://purl.org/pe-repo/ocde/ford#5.09.01